2, 4, 6‐Triphenylpyridinium: A Bulky, Highly Electron‐Withdrawing Substituent That Enhances Properties of Nickel(II) Ethylene Polymerization Catalysts. Issue 9 (15th January 2021) - Janeta, Mateusz; Heidlas, Julius X.; Daugulis, Olafs; Brookhart, Maurice
Abstract: The reactivity of Ni II and Pd II olefin polymerization catalysts can be enhanced by introduction of electron‐withdrawing substituents on the supporting ligands rendering the metal centers more electrophilic. Reported here is a comparison of ethylene polymerization activity of a classical salicyliminato nickel catalyst substituted with the powerful electron‐withdrawing 2, 4, 6‐triphenylpyridinium (trippy) group to the ‐CF3 analogue. The trippy substituent is substantially more electron‐withdrawing (σmeta =0.63) than the trifluoromethyl group (σmeta =0.43) which results in a ca. 8‐fold increase in catalytic turnover frequency. An additional advantage of trippy is the high steric bulk relative to the trifluoromethyl group. This feature results in a four‐fold increase in polymer molecular weight owing to enhanced retardation of chain transfer. A significant increase in catalyst lifetime is observed as well. Abstract : A 2, 4, 6‐triphenylpyridinium (trippy) group is used to enhance properties of nickel olefin polymerization catalysts. Comparison with the corresponding CF3 ‐substituted complex shows the advantages of catalysts possessing the new substituent. High steric bulk combined with powerful electron‐withdrawing properties of this substituent result in increased catalytic activity and polymer molecular weight for the trippy‐substituted complex.